The Link between Ankylosing Spondylitis, Crohn's Disease, Klebsiella, and Starch Consumption. (27th May 2013) - Rashid, Taha; Wilson, Clyde; Ebringer, Alan
Abstract : Both ankylosing spondylitis (AS) and Crohn's disease (CD) are chronic and potentially disabling interrelated conditions, which have been included under the group of spondyloarthropathies. The results of a large number of studies support the idea that an enteropathic pathogen, Klebsiella pneumoniae, is the most likely triggering factor involved in the initiation and development of these diseases. Increased starch consumptions by genetically susceptible individuals such as those possessing HLA-B27 allelotypes could trigger the disease in both AS and CD by enhancing the growth and perpetuation of the Klebsiella microbes in the bowel. Exposure to increased levels of these microbes will lead to the production of elevated levels of anti- Klebsiella antibodies as well as autoantibodies against cross-reactive self-antigens with resultant pathological lesions in the bowel and joints. Hence, a decrease of starch-containing products in the daily dietary intake could have a beneficial therapeutic effect on the disease especially when used in conjunction with the currently available medical therapies in the treatment of patients with AS and CD.